2018
DOI: 10.2147/ndt.s162760
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism in psychiatric inpatients: a chart review

Abstract: PurposeVenous thromboembolism (VTE) is the combination of pulmonary embolism (PE) and deep vein thrombosis. In recent years, VTE has been gaining attention in the field of psychiatry as it can cause sudden deaths in patients hospitalized in psychiatric departments. The purpose of this study was to investigate the incidence of VTE in psychiatric inpatients using contrast-enhanced computed tomography (CT).Patients and methodsAt the psychiatric department of the Akita University Hospital, NANOPIA® D-dimer was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 24 publications
0
27
0
2
Order By: Relevance
“…As stated above, this finding is also supported by de Hert et al (18). In contrast to these, the other studies observed that VTE occurred even when the restrained patients were heparinized or receiving other prophylactic measures (22, 39) and the importance of regular examination and treatment of thrombosis was emphasized (22).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As stated above, this finding is also supported by de Hert et al (18). In contrast to these, the other studies observed that VTE occurred even when the restrained patients were heparinized or receiving other prophylactic measures (22, 39) and the importance of regular examination and treatment of thrombosis was emphasized (22).…”
Section: Resultsmentioning
confidence: 97%
“…Analyzed with regard to their methodology, two studies were experimental RCTs that investigated coercive measures on healthy subjects (14, 15) with small sample sizes of 13 respectively six probands, 1 study was a case-control study (16), 11 studies were classified as epidemiological studies (1727), 12 as association studies (2839), and the majority as case series (40–59) and case reports (6080). A systematic quality assessment of the included studies as it is usually done with RCTs being included in meta-analyses (risk of bias) and calculation of risks was not possible due to the diverse methodology of the studies, with different designs, different investigated outcomes, and partly incomplete data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients can be older, may be physically restrained, medically restrained, or catatonic and therefore bed‐bound, or have dementia, all of which has been associated with an increased risk of pulmonary embolism 4 . One psychiatric hospital evaluating the incidence of venous thromboembolism among their patients found an overall incidence of 2.3% but a much higher rate amongst groups that were catatonic and/or restrained 5 . In that population, the majority of venous thromboembolisms that were found (76.9%) were pulmonary embolisms, 5 and there is a case report of a patient who died secondary to massive pulmonary embolism during psychiatric hospitalization 6 .…”
Section: Discussionmentioning
confidence: 99%
“…One psychiatric hospital evaluating the incidence of venous thromboembolism among their patients found an overall incidence of 2.3% but a much higher rate amongst groups that were catatonic and/or restrained 5 . In that population, the majority of venous thromboembolisms that were found (76.9%) were pulmonary embolisms, 5 and there is a case report of a patient who died secondary to massive pulmonary embolism during psychiatric hospitalization 6 . Even patients who were restrained and receiving prophylaxis to prevent venous thrombosis were still found to have venous thromboembolisms at a rate of 11.6% at one hospital in Japan 7 …”
Section: Discussionmentioning
confidence: 99%